Can evolutionary theories of dispersal and senescence predict postrelease survival, dispersal, and body condition of a reintroduced threatened mammal?. Issue 2 (30th December 2020) - Robinson, Natasha M.; Blanchard, Wade; MacGregor, Christopher; Brewster, Rob; Dexter, Nick; Lindenmayer, David B.
Abstract: Theories of dispersal and senescence (or aging) predict that dispersal, and ongoing survival and body condition, are influenced by evolutionary drivers, along with intrinsic and extrinsic factors. Such theories are relevant to translocations of animals where high mortality, loss of body condition, and dispersal beyond the area of release are commonly reported. However, these theories have rarely been tested using data from translocations. We explore whether theories of dispersal and senescence, together with biological knowledge and management interventions, can predict rates of postrelease dispersal, survival and change in body condition of a translocated endangered meso‐predator, the eastern quoll Dasyurus viverrinus . Captive‐bred quolls ( n = 60) from three sanctuaries were translocated to an unfenced, predator‐managed reserve (Booderee National Park) over 2 years (2018, 2019). Survival, dispersal and body mass were monitored via GPS/VHF tracking and targeted trapping for 45 days postrelease. We found support for the "social subordinate" hypothesis, with smaller quolls dispersing further. Consistent with theories of senescence and the biology of our species, survival was marginally greater for females, and females regained losses in body mass in both years following release. In contrast, males recovered body condition in the first but not the second release as this coincided with breeding. Quolls that originated from the mainland sanctuary were on average heavier at release and, after accounting for weight, dispersed further. Synthesis and applications . Using theory to test outcomes of wildlife translocations can provide insights into patterns across taxa and under different conditions, enabling useful improvements to future fauna translocations. This allows for better predictions to be made about the likelihood of success from proposed translocations, changes to planning to improve outcomes (e.g., modifying sex ratios, individual selection and release cohort), and improved animal welfare as fewer animals are subjected to trials. Abstract : We test the applicability of theories of dispersal and senescence (or ageing) in predicting postrelease dispersal, survival, and change in body condition of translocated fauna; we use the eastern quoll as a case study. We found support for the "social subordinate" hypothesis, with smaller quolls dispersing further. Consistent with theories of senescence and our species biology, survival was marginally greater for females, and females regained losses in body mass in both years following release. Integrating theory into practice enables improved understanding of species responses to management actions such as fauna translocations.